MODEL PEMBELAJARAN RESPONSI PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS MEDAN AREA - Fauji Wikanda (Yayasan Pendidikan Islam dan Multikultural, 2024)
Abstract: This research aims to describe and analyze the responsive learning model for Islamic religious education at Medan Area University. The research objects are students, lecturers and managers responding to Islamic religious education. The research method used is qualitative research providing data in the form of descriptions or written words. Data collection techniques were carried out by interviewing lecturers and administrators of Islamic religious education. Observations were also carried out to strengthen the validity of the interview. The research results show that the responsive learning model for Islamic religious education at Medan Area University is part of Islamic religious education lectures which are delivered in the form of discussions and practicums. Teaching materials in response to Islamic religious education include the character of istiqomah and honesty, responsibility, integrity, justice, positive attitude, compassion and patience, self-control, hard work and social instincts, full of gratitude, generosity and humility, himmah, wisdom. , and fathanah. Next, the practical material consists of thaharah, obligatory and sunnah prayers, fardhu kifayah, Hajj rituals, and preaching rhetoric. Keyword : Learning model, Response to Islamic Religious Education Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis model pembelajaran responsi pendidikan agama Islam di Universitas Medan Area. Objek penelitian adalah mahasiswa, dosen dan pengelola responsi pendidikan agama Islam. Metode penelitian yang digunakan adalah penelitian kualitatif memberikan data dalam bentuk uraian atau kata-kata tertulis.Teknik pengumpulan data dilakukan dengan cara wawancara terhadap dosen dan pengelola responsi pendidikan agama Islam. Observasi juga dilakukan untuk memperkuat validitas wawancara. Hasil penelitian menunjukkan bahwa model pembelajaran responsi pendidikan agama Islam di Universitas Medan Area merupakan bagian dari perkuliahan pendidikan agama Islam yang disampaikan dalam bentuk diskusi dan praktikum. Materi ajar responsi pendidikan agama Islam diantaranya tentang karakter istiqomah dan jujur, tanggung jawab, integritas, keadilan, sikap positif, rasa kasih dan kesabaran, pengendalian diri, kerja keras, dan naluri sosial, penuh syukur, kedermawanan, dan kerendahan hati, himmah, hikmah, dan fathanah, Selanjutnya materi praktikum berupa thaharah, salat wajib dan salat sunnah, fardhu kifayah, manasik haji, dan retorika dakwah. Kata Kunci: Model Pembelajaran, Responsi Pendidikan Agama Islam